Karakteristik Katarak Kongenital di RSUD Provinsi NTB Periode 2018-2019 - Salsabilla, Rani; Yuni Andari, Marie; Nasrul, Monalisa (Jurnal Syntax Fusion, 2021)
Congenital cataracts are the leading cause of blindness in children. Lens opacity in early life has the potential to cause permanent visual impairment if not treated promptly. Cataract surgery performed at the right time can prevent children from amblyopia (lazy eye). This study aims to determine the characteristics of congenital cataracts at the West Nusa Tenggara Provincial General Hospital in the 2018-2019 period. This research uses descriptive method. The data used is secondary data from medical records of congenital cataract patients at the West Nusa Tenggara Provincial General Hospital in the 2018-2019 period. In the 2018-2019 period, 40 children had congenital cataracts. Most of the cataract sufferers were women (52.5%); living outside the city of Mataram (92.5%) with an age distribution of under 12 months (95%) and the rest over 12 months. For infants under 12 months, 53 percent have been diagnosing at the age of 1-2 months. The characteristics of congenital cataracts found were generally bilateral (52.5%), had standard birth weight (52.5%), history of natural birth delivery (67.5%), and had other extraocular congenital abnormalities (72.5%). Most patients with congenital cataracts in the West Nusa Tenggara Provincial General Hospital have been diagnosing at a (pretty/moderately) early age of 1-2 months at the beginning of their lives. So, with appropriate and prompt therapy, hoping that it can reduce the risk of amblyopia.